Representations of Family Concept in Senior Preschool Age Children - Sakharova, Tatiana; Zhuravleva, Inna; Bataeva, Maria (Զանգակ հրատ.)
Peculiarities of representations of family concept in senior preschool-age children are considered in the article. The authors of the article define representations as a certain vision of the world and relationships in it that help an individual to adapt to the world around him. According to the authors, the style of child-parent relations has an impact on the formation of a child’s ideas about family. As a result of empiric research, the authors come to the conclusion that the personality-centred style of child-parent relationship fosters ideas of positive family relations in senior preschool-age children. The tolerant type of child-parent relations determines the formation of the concept of neutral family relations in older preschool children. The ego-isolated style of child-parent relationships contributes to the formation of negative ideas about family relationships in senior preschool children. The empirical research has shown the predominance of ideas about positive family relationships in senior preschool children. In general, children of senior preschool age include family members, people and animals who live together with the child in the representation of the family, describe joint recreation and pastime, note the care of themselves as a child and characterize the features of emotional relationships between themselves and other family members. All three types of family concepts’ representations are manifested both in boys and girls. It is possible to trace the tendency of the predominance of ideas about negative family relations in boys, the predominance of ideas about neutral family relations in girls of senior preschool age.
Keywords: Pedagogy